Magnetostratigraphy of the Triassic Moenkopi Formation From the Continuous Cores Recovered in Colorado Plateau Coring Project Phase 1 (CPCP‐1), Petrified Forest National Park, Arizona, USA: Correlation of the Early to Middle Triassic Strata and Biota in Colorado Plateau and Its Environs. Issue 9 (26th September 2021) - Haque, Ziaul; Geissman, John W.; Irmis, Randall B.; Olsen, Paul E.; Lepre, Christopher; Buhedma, Hesham; Mundil, Roland; Parker, William G.; Rasmussen, Cornelia; Gehrels, George E.
Abstract: The Colorado Plateau Coring Project Phase 1 (CPCP‐1) acquired three continuous drill cores from Petrified Forest National Park (PFNP), Arizona, U.S.A., two of which (CPCP‐PFNP13‐1A and CPCP‐PFNP13‐2B) intersected the Upper Triassic Chinle Formation, Lower(?)‐Middle Triassic Moenkopi Formation (MF) and Permian Coconino Sandstone. We examined both cores to construct a high‐resolution magnetostratigraphy of MF strata, and progressive demagnetization data yield well‐defined, interpretable paleomagnetic results. Each lithostratigraphic member of the MF (Wupatki, Moqui, and Holbrook members) contains authigenic and detrital hematite as the dominant magnetic carrier with distinguishing rock magnetic characteristics. Magnetostratigraphy of MF strata in both CPCP‐1 cores consists of six normal and six reverse polarity magnetozones, from the youngest to the oldest, MF1n to MF6r. Recent single‐crystal chemical abrasion–thermal ionization mass spectrometry (CA‐TIMS) U‐Pb data from a sample in magnetozone MF1n yield a latest Anisian/earliest Ladinian (241.38 ± 0.43 Ma) age. Correlation of the CA‐TIMS‐calibrated magnetostratigraphy with the astronomically tuned polarity timescale for the Middle Triassic deep‐marine Guandao (GD) section of South China ties the magnetozone MF1n with GD8 and MF6r with GD2r, and implies that the MF spans, at most, the earliest Anisian (Aegean) to latest Anisian (Illyrian)/earliest Ladinian stages (ca. 246.8 to 241.5 Ma). This age estimate for the MF suggests that the timespan of the regional, pre‐Norian disconformity is about 17 Ma, which demonstrates that MF vertebrate fossil assemblages in east‐central Arizona are millions of years (minimally 3–4 Ma) younger than previously suggested and are all Anisian in age, with no indications of substantial hiatuses in the MF section. Plain Language Summary: The Triassic Period, between about 252 and 201.5 million years ago, witnessed many significant Earth System events, including extreme temperature swings, high atmospheric carbon‐dioxide concentration, and biotic recovery from the Earth's greatest mass extinction at its beginning and another mass extinction at its end. This research is aimed at obtaining a high‐resolution magnetic polarity stratigraphy for the Moenkopi Formation based on two cores recovered from the Petrified Forest National Park, Arizona, U.S.A., to provide a robust age constraint of its constituent fossil assemblages that will allow a correlation across continents, document key biotic events, such as the recovery from the end‐Permian mass extinction, the diversification of reptiles, and the origin of dinosauromorphs. We have identified six magnetic reversal events during the deposition of the Moenkopi Formation rocks and suggest that these strata span, at most, ∼246.8 Ma to ∼241.5 Ma. This study also suggests that the time gap between the Moenkopi Formation and the overlying Chinle Formation, the home of the petrified forests, is about 17 Ma long. The revised age model of the Moenkopi Formation from this study will provide a high‐resolution age constraint for future paleoclimatic, biotic, and correlation studies of rocks from a similar age on a global basis. Key Points: Complete magnetostratigraphy of the entire Middle Triassic age Moenkopi Formation drilled at the Petrified Forest National Park, Arizona A high sampling frequency provides a comparison with polarity records from surface exposures elsewhere in the Colorado Plateau Revised estimated age of the Moenkopi Formation (ca. 246.8 Ma–241.5 Ma) requires a reinterpretation of its constituent fossil assemblages